ANALISIS PELAKSANAAN PEMBERIAN MOTIVASI DAN PENGARUHNYA TERHADAP KUALITAS PELAYANAN BISNIS JASA PENGIRIMAN ( Kasus PT. Pos Indonesia (Persero) cabang Pekanbaru) - Mitra Elda Silvia; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aims to determine the effect of the implementation of motivation on the quality of service at PT. Pos Indonesia (Persero) Pekanbaru branch. Implementation of motivation as a variable X and the quality of service as a variable Y. This study refers to the ERG theory of Clayton Alderfer (1972) which says there are three groups, namely the need for existence, relatedness and growth, where samples were used that customer PT. Pos Indonesia (Persero) Pekanbaru branch with respondents as many as 100 customers. To determine the number of samples used formula slovin, while the collection of data used are observation, interviews and questionnaires. The measurement technique using a Likert scale with answers which were given a score of 1-5, while the statistical test equipment used is linear regression, the coefficients of determination and t test. From the discussion that is seen from the need for existence, relatedness and growth undertaken by PT. Pos Indonesia (Persero) Pekanbaru branch can be seen that the implementation of the provision of motivation have been effective and well categorized and significant effect on the quality of service.Keywords : Motivation , Quality of Service , existence , relatedness and growth